Karakteristik Anomali Magnetik dari Metode Reduksi ke Kutub dan Reduksi ke Ekuator pada Struktur Sesar - Aulia Huda Pinandita; Wahyu Sutresno (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
Magnetic interpretation has its own challenges due to the bipolar nature of the Earth's magnetic field. So it is necessary to apply the reduction to poles and reduction to equator methods to make structure’s identification easier. In this research, magnetic data collection has been carried out in Lembang, West Java with the aim of validating the synthetic model anomaly results with field data to identify the position of the Lembang fault structure. By applying the pole reduction and equator reduction methods to magnetic anomaly field data, the structure of the Lembang Fault can be identified well and the anomaly character obtained from each method.